2001
DOI: 10.1055/s-2001-14838
|View full text |Cite
|
Sign up to set email alerts
|

Association between the P12A and c1431t polymorphisms in the peroxisome proliferator activated receptor γ (PPARγ) gene and type 2 diabetes

Abstract: Variation in the peroxisome proliferator-activated receptor gamma (PPAR gamma) gene may play a role in the development of type 2 diabetes mellitus. Therefore we investigated the association between the P12A and c1431t polymorphisms in the PPAR gamma gene and type 2 diabetes. The incidence of the P12A polymorphism was determined by PCR-RFLP and the c1431t by single-strand conformation polymorphism analysis in 219 patients with, and 429 without type 2 diabetes. The frequency of the A allele of P12A polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 14 publications
3
34
1
1
Order By: Relevance
“…In line with our study, the Ala12 allele has been reported to associate with type 2 diabetes in Canadian Oji-Cree women (24). Similarly, Evans et al (25) found an association between the Ala12 allele and type 2 diabetes. Hasstedt et al (26) studied members of familial type 2 diabetic kindreds and reported that the proportion of individuals with type 2 diabetes increased with the number of Ala12 alleles, although the result was not statistically significant.…”
Section: Discussionsupporting
confidence: 79%
“…In line with our study, the Ala12 allele has been reported to associate with type 2 diabetes in Canadian Oji-Cree women (24). Similarly, Evans et al (25) found an association between the Ala12 allele and type 2 diabetes. Hasstedt et al (26) studied members of familial type 2 diabetic kindreds and reported that the proportion of individuals with type 2 diabetes increased with the number of Ala12 alleles, although the result was not statistically significant.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we found that the allele frequency of rs3856806T in the Kazakh control group was 17%. This value is close to the allele frequency of rs3856806T in the Australian population (16.3%; Evans et al, 2001), is higher than that in the South American (13%; Haseeb et al, 2009), Indian (12.3%;Costa et al, 2009), and Italian and French populations (13.3%; Hasstedt et al, 2001), but lower than that among the Han population (21.2%; Liu et al, 2008). Studies examining the relationship between the rs3856806 polymorphism and MS suggest that individuals carrying the T allele show clearly reduced rates of lipid metabolism disorders and high blood pressure, obesity, and diabetes (Chen et al, 2006;Jaziri et al, 2006;Gaulton et al, 2008;Cho et al, 2009;Gallicchio et al, 2009;Bego et al, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…Although a meta-analysis evaluating 16 published studies involving more than 3,000 individuals reported a significant increase in diabetes risk (1.25-fold) associated with the most common Pro allele (15), subsequent studies failed to confirm this association (16,17). On the other hand, although it has been postulated that PPAR ␥ may play an im-portant role in lipid metabolism, directly or by inducing the transcription of target genes (18,19), to date, results from studies examining the association between PPAR ␥ 2 variants and lipid profiles are scarcer and also inconsistent (3,13,(20)(21)(22)(23).…”
mentioning
confidence: 98%